Perencanaan Dan Perancangan Pasar Ikan Di Desa Teluk Kecamatan Labuan Kabupaten Pandeglang Banten - erik erik redianto; Sri Kurniasih (MAESTRO, 2019)
A marine sale and purchase facility that has a clear vision, mission, goals and objectives, namely to develop and support national development in order to realize Indonesia as a global maritime axis by sovereign, independent and sustainable management of marine and fishery resources for people's prosperity. maritime and fisheries development must be carried out by all stakeholders to change a situation into a better condition by utilizing marine and fisheries resources optimally, efficiently and effectively and with the ultimate goal of improving community welfare in a sustainable manner. So that it can realize maritime and fisheries development that is able to maintain the area of economic independence by securing fisheries resources and reflecting the personality of Banten province as an archipelago / water area. Planning Building and Fish Market Designing in Teluk Subdistrict, Labuan Subdistrict, Pandeglang District, BANTEN, incorporates the concept of Metaphoric Architecture. The concept of Metaphor Architecture is a figure of speech or form expression, manifested in a building in the hope that it will give rise to responses from people who enjoy or use their work. The application of the Metaphoric Architecture to the Fish Market in Labuan village is very suitable because the building will be built to support buildings that require building materials and adjustments to the surrounding environment. So later the Pasar Ikan building will look more artistic with the use of materials and forms that also aim to attract more visitors.Keywords: Fish Market, Labuan Sub-District, Labuan Village, Metaphorical Architecture